2017
DOI: 10.3390/en10010142
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Adsorption, Diffusion and Permeation Selectivity of Shale Gas in Organics

Abstract: Abstract:As kerogen is the main organic component in shale, the adsorption capacity, diffusion and permeability of the gas in kerogen plays an important role in shale gas production. Based on the molecular model of type II kerogen, an organic nanoporous structure was established. The Grand Canonical Monte Carlo (GCMC) and Molecular Dynamics (MD) methods were used to study the adsorption and diffusion capacity of mixed gas systems with different mole ratios of CO 2 and CH 4 in the foregoing nanoporous structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
54
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 56 publications
10
54
0
2
Order By: Relevance
“…In addition to experimental studies, molecular simulation is considered as an effective tool to gain microscopic insights into complex physical phenomena or processes in many research areas [20][21][22][23][24]. The adsorption behaviors in nanopores of shale reservoirs were investigated via molecular simulation by many researchers [25][26][27][28]. The effects of temperature, pressure, and pore size on the adsorption performance of pure methane and a CO 2 /CH 4 mixture in the slit pore of shale formations were examined.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to experimental studies, molecular simulation is considered as an effective tool to gain microscopic insights into complex physical phenomena or processes in many research areas [20][21][22][23][24]. The adsorption behaviors in nanopores of shale reservoirs were investigated via molecular simulation by many researchers [25][26][27][28]. The effects of temperature, pressure, and pore size on the adsorption performance of pure methane and a CO 2 /CH 4 mixture in the slit pore of shale formations were examined.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al have shown that there is a critical pore size that affects the adsorption of coalbed methane during the water injection process (Zhao et al 2018a). Wang et al (2017) have studied the effects of the competitive adsorption of methane and carbon dioxide on the adsorption of shale gas (Wang et al 2017). They found that the organic pores (pores in organic matter) have a higher adsorption capacity for CO 2 compared to methane although the self-diffusion of methane is larger than that of CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Gas flows in tight porous media have recently attracted much attention because they are widely applied in engineering fields, such as oil-gas field development, chemical processes, new energy development, and so on. The wide applications of gas flows in tight porous media also stimulate great interest in experimental and theoretical studies [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Gas flow in porous media usually involves three scales: Pore scale, representative elementary volume (REV) scale, and domain scale [ 14 ].…”
Section: Introductionmentioning
confidence: 99%